Perceived Changes in Anxiety Symptom Burden During Treatment with Bryophyllum pinnatum: A Prospective, Single-Arm Study - Tiffany Huber; Daniel Krüerke; Timotheus Haeck; Markus Weber; Matthias Kröz; Markus Schlemmer; Ana Paula Simões-Wüst (MDPI AG, 2024)
Background/Objectives: Bryophyllum spp. preparations are widely used in Anthroposophic Medicine, most often for mental and behavioral disorders, including anxiety. Studies in animals revealed various anxiolytic and neurosedative effects for Bryophyllum pinnatum. We set out to investigate the effectiveness of Bryophyllum 50% chewable tablets, a product registered without indication by means of notification in Switzerland, in the treatment of anxiety symptoms in psychiatric and psychosomatic patients. Methods: A total of 99 patients with anxiety symptoms were recruited from the waiting list for an inpatient stay at the hospital "Klinik Arlesheim", Department of Psychiatry and Psychosomatics; of these, 54 completed the study and returned fully completed questionnaires. Patients were treated with Bryophyllum 50% chewable tablets (350 mg tablets, made from leaf press juice, 3 × 2 per day; Weleda AG Arlesheim, Switzerland) and filled out questionnaires at baseline and after two and three weeks of tablet intake. The primary endpoint of the study was the change in anxiety symptoms measured with the Beck Anxiety Inventory (BAI). Results: A clinically relevant decrease in BAI score from baseline (27.4 ± 12.0) to after two (22.4 ± 12.1; p < 0.001) and three (20.6 ± 12.9; p < 0.001) weeks of treatment was observed. Additional improvements were observed in the secondary endpoints (including in depression, sleep quality, and stress); tolerability and compliance were very good. Conclusions: The results suggest that Bryophyllum 50% chewable tablets have beneficial effects on anxiety-related symptoms. Since the study design does not allow us to conclude causality between treatment and observed improvements, a randomized clinical trial is urgently needed.